Proceedings of the International Conference on Management, Computer and Education Informatization 2015
DOI: 10.2991/mcei-15.2015.61
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis of the Impact of the Employment Stability on Income of the Floating Populations in the Pearl River Delta Region

Abstract: Abstract-China has the largest floating population in the world, whose employment situation is not optimistic, and the employment stability is poor. From the view of labor search theory, the employee may switch his job to get higher income by searching in the labor market; from the view of human capital theory, stable employment can improve the level of human capital and thus increase their income for workers. What is the impact of the employment stability on income of the floating population in the PRD? This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In terms of employment, employment opportunities in first-tier cities were more attractive to the floating population ( 67 ), and it was more necessary to protect the basic rights and interests of new industry workers, such as income, and maintain their employment stability by building harmonious labor relations ( 68 ). In addition, it was necessary to improve the affordability of urban housing ( 69 ) and bring more new industry workers into the security scope of public rental housing and the community service system.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of employment, employment opportunities in first-tier cities were more attractive to the floating population ( 67 ), and it was more necessary to protect the basic rights and interests of new industry workers, such as income, and maintain their employment stability by building harmonious labor relations ( 68 ). In addition, it was necessary to improve the affordability of urban housing ( 69 ) and bring more new industry workers into the security scope of public rental housing and the community service system.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of individual action depends on the future economy (Esteban, 2017). The longer a migrant worker intends to stay in the inflow city, the greater their motivation to improve human capital in their current jobs due to their positive expectations regarding local economic prospects (Guan, 2015). The positive coefficient of spandt shows that migration is a valuable investment (Oded & David, 1985).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding mobility characteristics, features such as the original wage status before migrant flow, farmland possession before migrant flow, stability after migrant flow, the flow of family members, the frequency of mobility, the distance of mobility, mobility status across the administrative regions, occupational mobility, and purpose of migration play major roles in migrant workers' income (Yin et al., 2020). Concerning employment characteristics, elements that influence migrant workers' income include the employment situation, work type, occupational type, formality of the work unit, the work unit's scale, hours of work, the labor contract signing rate, and employment stability (Guan, 2015; Wu & Marette, 2020). (b) The social and economic environment that primarily affects migrant workers’ income includes the social system, economic environment, and social integration.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This suggests that being financially capable can also influence one's decision to pursue self-employment opportunities. In addition, according to Guan [53], employment stability, as determined by an individual's employment classification, can significantly impact income stability. Research has shown that stable employment is associated with increased income levels for workers, as it allows for the accumulation of human capital over time, leading to higher earnings.…”
Section: Theme 3: Income Stability and Job Securitymentioning
confidence: 99%